Performance of Female Garut Lambs Fed Diet in Different Ratio of Protein and Total Digestible Nutrients (PERFORMANS ANAK DOMBA GARUT BETINA MASA PERTUMBUHAN YANG DIBERI PAKAN DENGAN IMBANGAN PROTEIN DAN TOTAL DIGESTIBLE NUTRIENT BERBEDA) - Hernaman, Iman; Ayuningsih, Budi; Ramdani, Diky; Maisarah, Mesa; Siswoyo, Siswoyo (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.568, 2019)
The study aimed to study the effect of protein and total digestible nutrients on performance of female Garut lambs. A total of 20 female Garut lambs aged 7-8 months at averaged body weight 15.72 ± 1.33 kg were allocated randomly into four treatment diets with different crude protein and total digestible nutrients ratios.  The treatments were:  T1 = 11.53%:63.13%; T2 = 10.78%:70.06%; T3 = 13.54%:63.18%; and T4 = 13.67%:69.18%. Each treatment was replicated five times. The research was conducted experimentally for 12 weeks and the collected data were analyzed by Duncan’s multiple range test. The dry matter intake was significantly (p<0.05) higher in the treatments of T1 (707.70 g/d), T2 (677.71 g/d) and T4 (687.91 g/d) compared to T3 (587.01 g/d). The highest (p<0.05) average daily gain and the smallest (p<0.05) feed conversion ratio were significantly obtained by T4 (89.88 g/d and 7.75). Dry matter digestibility and organic matter digestibility was significantly (p<0.05) greater for T2 (63.93% and 64.10%) and T4 (59.73% and 65.14%) compared to T1 (49.98% and 55.34%) and T3 (44.68% and 50.60%) treatments. Based on the results, it can be concluded that T4 or the diet containing 13.67% crude protein and 69.18% total digestible nutrients yielded the best performance.